Cropland displacement contributed 60% of the increase in carbon emissions of grain transport in China over 1990–2015 - Zuo, Chengchao; Wen, Cheng; Clarke, Grahm; Turner, Andy; Xinli Ke; You, Liangzhi; Tang, Lanping (Springer, 2023)
Rapid urbanization and population growth have increased the need for grain transportation in China, as more grain is being consumed and croplands have been moved away from cities. Increased grain transportation has, in turn, led to higher energy consumption and carbon emissions. Here we undertook a model-based approach to estimate the carbon emissions associated with grain transportation in the country between 1990 and 2015. We found that emissions more than tripled, from 5.68 million tons of CO2 emission equivalent in 1990 to 17.69 million tons in 2015. Grain production displacement contributed more than 60% of the increase in carbon emissions associated with grain transport over the study period, whereas changes in grain consumption and population growth contributed 31.7% and 16.6%, respectively. Infrastructure development, such as newly built highways and railways in western China, helped offset 0.54 million tons of CO2 emission equivalent from grain transport. These findings shed light on the life cycle environmental impact within food supply chains.